Evaluasi Perubahan Perilaku Petani dengan Penyuluhan dan Tanpa Penyuluhan Pengolahan Lahan Bawang Merah - Khairi, Ahmad (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
Shallots are one of the seven essential commodities that impact farmers' livelihoods, the overall economy, and inflation rates, thus requiring excellent and effective farm management. However, many farmers complain of declining production yields. Onion yields in the first growing season resulted in relatively high production, but in the second and third growing seasons, the yield levels decreased. This happens because of land damage due to residue from agricultural input chemicals. Therefore, extension workers are needed to guide and counsel farmers so that the growth of shallot production continues to increase. This study obtained sample data from farmers from Solok Regency, West Sumatra Province, Nagari alahan panjang and cold water without counselling, Nagari alahan panjang and cold water with counselling and farmer group members. The results of this study state that there is a difference in the score difference of shallot farmers' behaviour with extension and without extension of land processing, where the average score of farmers' behaviour with extension is higher than without extension. From the aspect of knowledge, the difference in score is 8.39, the attitude aspect is 8.98, and the skill aspect is 10.73. This means that the behaviour of farmers with extension is better than that of farmers without extension regarding knowledge, attitudes, and skills.